Aerodynamic performance and wake development of NACA 0018 airfoil with serrated gurney flaps - Zheng, Zhehui; Chen, Liu (Frontiers in Energy Research, 2024)
Improving the aerodynamic performance of the airfoil is important for optimising the rotor efficiency of the vertical axis wind turbines. As a simple passive control method, the Gurney flap is widely used to improve the aerodynamic performance of airfoils. In this paper, we study the impact of applying a novel serrated gurney flap with different heights on the NACA 0018 airfoil. An improved delayed detached eddy simulation method is adopted to investigate the lift-enhancing mechanism of the serrated gurney flap and the evolution of the downstream vortex system. The results show that the serrated gurney flap can effectively increase the airfoil lift coefficient and the lift-to-drag ratio. The improvement of the serrated gurney flap on the aerodynamic performance of the airfoil is more pronounced at moderate angles of attack. Further analysis of the downstream wake shows that a pair of vortices wraps over both sides of the airfoil and rotates perpendicular to the wake flow, which is produced by the columnar vortex upstream of the flap. These vortices mixed with the wake and accelerated the dissipation of the separated vortex on the suction surface of the airfoil.